2020
DOI: 10.1186/s12866-020-01971-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of capsulated Acinetobacter baumannii using a density-dependent gradient test

Abstract: Background Gram-negative bacterial capsules are associated with production of carbohydrates, frequently resulting in a mucoid phenotype. Infections caused by capsulated or mucoid A. baumannii are associated with increased clinical severity. Therefore, it is clinically and epidemiologically important to identify capsulated A. baumannii. Here, we describe a density-dependent gradient test to distinguish between capsulated and thin/non-capsulated A. baumannii. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 28 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Isolates were categorized by visual inspection as mucoid or nonmucoid [ 18 ]. The phenotype was also evaluated according to several colony morphology parameters, including texture, elevation, margin, size, and shape [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates were categorized by visual inspection as mucoid or nonmucoid [ 18 ]. The phenotype was also evaluated according to several colony morphology parameters, including texture, elevation, margin, size, and shape [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of capsule was confirmed using a density-dependent gradient test [ 18 ]. Results were read by visual observation: A bacterial band that migrated to the bottom phase of the gradient was classified as a noncapsulated strain, while a bacterial band that concentrated in the top phase was suspected to be a capsulated strain.…”
Section: Methodsmentioning
confidence: 99%
“…For qualitative estimation of capsule levels, we used density gradient centrifugation as previously described 101 , which is based on the effect of cell-associated capsule on bacterial density. Briefly, 1 ml of overnight grown cultures were centrifuged, washed with PBS and resuspended in 1 ml PBS.…”
Section: Biofilm Formation and Capsule Synthesismentioning
confidence: 99%
“…Previous work revealed that wild-type VIR-O cells exhibit a 2fold increase in capsule compared with the wild-type AV-T (Chin et al, 2018). We utilized a Percoll density gradient, a method that was recently described as a method to separate A. baumannii strains by capsule level (Kon et al, 2020), to compare capsular polysaccharide levels in AV-T D1132 to wild-type VIR-O and AV-T cells. As seen in Figure 3C, the gradient is able to distinguish between capsule levels of the wild-type VIR-O and AV-T variants, with the AV-T cells migrating significantly further than the VIR-O cells.…”
Section: Deletion Of 1132 In the Av-t Background Increases Capsulementioning
confidence: 99%
“…Method slightly modified from Kon et al (2020). Cell cultures of VIR-O, AV-T, and AV-T D1132 were grown in 2 mL LB from pure frozen stocks to OD 600 ~0.6 (shaking, 37°C).…”
Section: Percoll Density Gradientmentioning
confidence: 99%